Holistic-Integrative Islamic Economics: Synergy of Revelation, Reason, and Social Reality in the Management of Zakat and Productive Waqf - Royani Royani; Rohwan Rohwan; Mugni Muhit (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the strengthening of productive zakat and waqf governance through a holistic-integrative Islamic economic approach in Indonesia. The background of this study is based on the substantial potential of zakat and waqf that has not been optimally realized due to weak governance and the gap between normative, rational, and empirical dimensions in practice, particularly within Islamic Higher Education Institutions (PTKI). This research employs a qualitative literature review method with a thematic content analysis approach, drawing on recent scholarly articles and policy documents. The findings indicate that zakat functions as a short-term redistributive instrument, while productive waqf serves as a long-term development instrument, both of which are complementary. In addition, digitalization enhances transparency and efficiency; however, its effectiveness depends on the quality of governance. The study also finds that zakat and waqf are aligned with maqasid al-shariah and the Sustainable Development Goals (SDGs), and that knowledge integration within PTKI provides an important epistemological foundation for their management. The novelty of this research lies in the development of a holistic-integrative Islamic economic model that connects revelation, reason, and social reality within a unified systemic framework. This study concludes that the integration of productive zakat and waqf can improve the effectiveness of socio-economic development, although further empirical validation is required.